Maternal awareness regarding vitamin D supplementation and its deficiency among their infants in a tertiary care hospital, Puducherry: a cross-sectional study - R., Harivignesh; Amarnath; S., Rajini (International Journal Of Community Medicine And Public Health, 2026)
Background: Vitamin D deficiency is a common public health problem affecting mothers and infants, even in sun-rich countries like India. Maternal awareness plays a key role in preventing deficiency and its complications in infants. This study aimed to assess maternal awareness regarding vitamin D supplementation and its deficiency among infants, and to determine the association with sociodemographic factors. Methods: A hospital-based cross-sectional study was conducted among 200 postnatal mothers attending the Paediatrics OPD of a private medical college in Puducherry from September to December 2025. Participants were selected using systematic random sampling. Data were collected using a pre-tested, self-administered questionnaire via an online platform. Descriptive statistics were expressed as frequencies and percentages, and associations were tested using the Chi-square test (p<0.05 considered significant). Results: Among participants, 78.0% had heard about vitamin D, with doctors as the main information source (74.3%). While 47.0% recognized its role in bone health, 21.0% lacked knowledge of its benefits. Only 39.0% and 23.0% reported vitamin D supplementation during pregnancy and lactation, respectively. However, 89.0% provided supplements to their infants, though only 24.0% did so regularly. Most mothers (87.0%) exposed infants to sunlight. Significant associations were observed between knowledge and age (p=0.035), education (p<0.001), residence (p<0.001), family type (p=0.007), and housing (p<0.001). Conclusions: Despite moderate awareness, gaps in knowledge and practices persist. Strengthening maternal education and counselling is essential to improve vitamin D supplementation and reduce deficiency among infants.